Analysis of sodium hypochlorite effect on dentin structural components - Z. S. Khabadze; Ju. A. Generalova; V. S. Shubaeva; F. R. Ismailov; A. A. Nedashkovsky; M. G. Sheroziia; Kh. R. Khumgaeva (LLC "Endo Press", 2020)
The aim of this review article is detailed analyzation of the effect of sodium hypochlorite on the structural components of dentin. This compound is one of the strongest antimicrobial medicines for root canal treatment. However, sodium hypochlorite in certain concentrations has a detrimental effect on dentin, which leads to the loss of its physicochemical properties.Materials and methods. The study of publications was produced in the electronic databases such as Google Scholar, PubMed and ScienceDirect in the course of a systematic review of the literature. Included articles contain information about the on the effect of sodium hypochlorite on the structural components of dentin and the harmful effects of medicines for root canal treatment on organic elements.Results. 67 articles were viewed during the rview. After analyzing the literature for inclusion criteria, the total number of publications has become 43.Conclusions. According to the literature, it can be assumed that an increase in sodium hypochlorite concentration and its exposure time can lead to depletion of dentin organic matrix, which in turn, is responsible for the root fracture.